Role of Mineralocorticoid and Angiotensin Type 1 Receptors in the Paraventricular Nucleus in Angiotensin-Induced Hypertension - Burke, Sandra L.; Barzel, Benjamin; Jackson, Kristy L.; Gueguen, Cindy; Young, Morag J.; Head, Geoffrey A. (Frontiers in Physiology, 2021)
The hypothalamic paraventricular nucleus (PVN) is an important site where an interaction between circulating angiotensin (Ang) and mineralocorticoid receptor (MR) activity may modify sympathetic nerve activity (SNA) to influence long-term elevation of blood pressure. We examined in conscious Ang II-treated rabbits, the effects on blood pressure and tonic and reflex renal SNA (RSNA) of microinjecting into the PVN either RU28318 to block MR, losartan to block Ang (AT1) receptors or muscimol to inhibit GABAA receptor agonist actions. Male rabbits received a moderate dose of Ang II (24ng/kg min-1 subcutaneously) for 3 months (n=13) or sham treatment (n=13). At 3 months, blood pressure increased by +19% in the Ang II group compared to 10% in the sham (P=0.022) but RSNA was similar. RU28318 lowered blood pressure in both Ang II and shams but had a greater effect on RSNA and heart rate in the Ang II-treated group (P<0.05). Losartan also lowered RSNA, while muscimol produced sympatho-excitation in both groups. In Ang II-treated rabbits, RU28318 attenuated the blood pressure increase following chemoreceptor stimulation but did not affect responses to air jet stress. In contrast losartan and muscimol reduced blood pressure and RSNA responses to both hypoxia and air jet. While neither RU28318 nor losartan changed the RSNA baroreflex, RU28318 augmented the range of the heart rate baroreflex by 10% in Ang II-treated rabbits. Muscimol, however, augmented the RSNA baroreflex by 11% in sham animals and none of the treatments altered baroreflex sensitivity. In conclusion, 3 months of moderate Ang II treatment promotes activation of reflex RSNA principally via MR activation in the PVN, rather than via activation of AT1 receptors. However, the onset of hypertension is independent of both. Interestingly, the sympatho-excitatory effects of muscimol in both groups suggest that overall, the PVN regulates a tonic sympatho-inhibitory influence on blood pressure control.